2021
DOI: 10.1111/jocn.15669
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the advanced practice epilepsy nurse: A comparative study between two countries

Abstract: Background: Europe has recently faced the challenge of providing high-quality care for patients with epilepsy, a disease that generates many health demands. In some countries, such as the United Kingdom, advanced practice nursing is well established and could serve as a guide for implantation in countries where it is still in development, as is the case of Spain.Design: A multicentre cross-sectional descriptive cohort study compared differences in the roles of advanced practice nurses in Spain and the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although the changes in competence among individuals with different CNS levels over two years varied, their clinical practice competence levels all improved according to self-evaluation, with advanced-level CNSs improving the most. Clinical practice or direct clinical care was the most consolidated dimension of CNSs (20); a possible explanation is that direct care is the most traditional nursing role and essence of nursing practice. These ndings are consistent with those of other international and domestic studies investigating advanced practice nursing performance, which revealed that CNSs were most frequently involved in providing direct nursing services because of their expertise in speci c domains (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Although the changes in competence among individuals with different CNS levels over two years varied, their clinical practice competence levels all improved according to self-evaluation, with advanced-level CNSs improving the most. Clinical practice or direct clinical care was the most consolidated dimension of CNSs (20); a possible explanation is that direct care is the most traditional nursing role and essence of nursing practice. These ndings are consistent with those of other international and domestic studies investigating advanced practice nursing performance, which revealed that CNSs were most frequently involved in providing direct nursing services because of their expertise in speci c domains (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Although the contribution made by APNs has been studied in various settings, ranging from primary to specialised care, using indicators that directly reflect APN care [46,48,49,60] the role and importance of these professionals in the Spanish health system have yet to be fully determined. Thus, while some institutions have incorporated nurses with advanced skills, especially in the care of patients with chronic diseases [50,60], their status is neither well known nor formally regulated [61]. Our study shows that the incorporation of APHNs enhances clinical outcomes, and therefore it would be useful to conduct cost-effectiveness studies in this field, as has been proposed elsewhere [47,49,50,62].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly in relation to working practices, with the absence of national competency frameworks in epilepsy care, standardised speciality practice and job titles, and limited understanding of the EN scope of practice. Ultimately, this can impact skill development, career progression, and workforce planning (Epilepsy Nurse Specialist Association, 2012; Gardner et al, 2016;Higgins et al, 2019aHiggins et al, , 2019bLocatelli et al, 2021;Manzanares et al, 2021). ENs who predominantly work in the NFP sector faced additional challenges in their role working with a disconnected network of care and siloed governance structures across Australia related to the fragmented health and social care systems (Higgins et al, 2020;Schroeder & Cutler, 2021).…”
Section: Nurse-led Helplinementioning
confidence: 99%